Detection of CRISPR cassettes and cas genes in the Arabidopsis thaliana genome - Yu. M. Konstantinov; I. S. Petrushin (Вавиловский журнал генетики и селекции)
The state of the art in the evolution of plant viruses allows the genetic foundations of antiviral immunity in higher (including the most important crops) plants to be categorized as one of the most pressing issues of genetics and selection. According to the endosymbiotic theory, mitochondria descended from alphaproteobacteria that had been absorbed but not degraded by the host cell. The discovery of CRISPR-Cas systems (clustered regularly interspaced short palindromic repeats (CRISPR)-associated proteins), which implement the adaptive immunity function in prokaryotes, raises the question whether such a mechanism of antiviral protection could be caught up by evolution and used by representatives of eukaryotes (in particular, plants). The purpose of this work was to analyze the complete sequences of nuclear, mitochondrial, and chloroplast genomes of Arabidopsis thaliana in order to search for genetic elements similar to those in CRISPR-Cas systems of bacteria and archaea. As a result, in silico methods helped us to detect a locus of regularly intermittent short direct repeats in the mitochondrial genome of A. thaliana ecotypes. The structure of this locus corresponds to the CRISPR locus of the prokaryotic adaptive antiviral immune system. The probable connection between the locus found in the mitochondrial genome of the higher plant and the function of adaptive immunity is indicated by a similarity between the spacer sequences in the CRISPR cassette found and the genome of Cauliflower mosaic virus affecting Arabidopsis plants. Sequences of repeats and spacers of CRISPR cassettes in Arabidopsis C24 and Ler lines are perfectly identical. However, the locations of the CRISPR locus in the mitochondrial genomes of these lines differ significantly. The CRISPR cassette in the Col-0 line was found to be completely broken as a result of four deletions and one insertion. Although cas genes were not detected in the mitochondrial genome of the studied Arabidopsis ecotypes, their presence was detected in the nuclear genome. Both cas genes and numerous CRISPR cassettes were found on all the five chromosomes in the nuclear genome of the Col-0 ecotype. The results suggest the existence of a system of adaptive immunity in plants, which is similar to the CRISPR immunity of bacteria and archaea.